INTEGRASI HUNIAN DALAM TOD UNTUK MENGATASI PERMASALAHAN TRANSIT KAWASAN PASAR LAMA, TANGERANG - Oscar Tanudjaja; Felia Srinaga; Alvar Mensana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2018)
Title: Residential Integration in TOD to Overcome the Transit Problem in Pasar Lama Area, Tangerang The Pasar Lama (Old Town Market) area is known as a highly developing area in the city of Tangerang. This area facilitated with a commuter train station used by people commuted from Tangerang to Jakarta in daily basis – both for transitting and shopping purposes. Tangerang Station is the main train station for commuters’ from-and-to Jakarta; therefore, urban issues arise in the main urban nodes of the area, specifically the main boulevard near the station and the market. Issues such as transportation traffic, pedestrian congestion, informal street-vendors activities, and the arrangement of residential areas are major concern that needs to be addressed in the purpose of creating a good urban public space in the region. The solution to overcome this problem is to apply a concept for a TOD (Transit Oriented Development). TOD is a sustainable transportation system approach that provides accessibility and alternative modes of transportation. With the implementation of TOD in the transit station area, it is expected that the entire Pasar Lama area will be developed and created a good urban public space. This research study aims to answer several research questions, for instance: how does the concept of the TOD is able to integrate a residential program into the development and create a successful an urban public space as a transit area in the area of Pasar Lama, Tangerang. This research begins with context analysis based on several theories about urban dimension, human scale and key factors of a TOD. Precedent studies and observations on surrounding site, serve as references in analyzing and proposing draft concepts for this particular neighborhood. This research study will have an outcome in the form of design concept proposal that allow TOD to incorporate residential, parking, commercial, and open space as one district to revitalize the congested neighborhood in the Pasar Lama area, Tangerang.